Atomic Ni and Cu co-anchored 3D nanoporous graphene as an efficient oxygen reduction electrocatalyst for zinc–air batteries. Issue 24 (11th June 2021) - Cheng, Yongtai; Wu, Haofei; Han, Jiuhui; Zhong, Siying; Huang, Senhe; Chu, Shufen; Song, Shuangxi; Reddy, Kolan Madhav; Wang, Xiaodong; Wu, Shaoyi; Zhuang, Xiaodong; Johnson, Isaac; et al.
Abstract : Important progress is reported in the development of dual single-atom transition metal co-anchored catalysts, CuN x and NiN x moieties anchored on 3D nanoporous graphene, with superior ORR activities and durability for zinc–air batteries. Abstract : Highly active, cost-effective and durable electrocatalysts for the oxygen reduction reaction (ORR) are critically important for renewable energy conversion and storage. Here we report a 3D bicontinuous nitrogen doped nanoporous graphene electrocatalyst co-anchoring with atomically dispersed nickel and copper atoms ((Ni, Cu)–NG) as a highly active single-atom ORR catalyst, fabricated by the combination of chemical vapor deposition and high temperature gas transportation. The resultant (Ni, Cu)–NG exhibits an exceptional ORR activity in alkaline electrolytes, comparable to the Pt-based benchmarks, from the synergistic effect of the CuN x and NiN x complexes. Endowed with high catalytic activity and outstanding durability under harsh electrochemical environments, rechargeable zinc–air batteries using (Ni, Cu)–NG as the cathodes show excellent energy efficiency (voltage gap of 0.74 V), large power density (150.6 mW cm −2 at 250 mA cm −2 ) and high cycling stability (>500 discharge–charge cycles at 10 mA cm −2 ). This study may pave an efficient avenue for designing highly durable single-atom ORR catalysts for metal–air batteries.